COX-2 inhibition with rofecoxib does not increase intestinal permeability in healthy subjects: a double blind crossover study comparing rofecoxib with placebo and indomethacin. (1st October 2000) - Sigthorsson, G; Crane, R; Simon, T; Hoover, M; Quan, H; Bolognese, J; Bjarnason, I
Abstract : BACKGROUND: Acute and chronic use of non-steroidal anti-inflammatory drugs can increase intestinal permeability. Rofecoxib, which selectively inhibits cyclooxygenase 2 (COX-2), is a novel anti-inflammatory drug with the potential to produce minimal gastrointestinal toxic effects while retaining clinical efficacy. AIMS: To assess the potential for rofecoxib to affect the intestine adversely, in comparison with placebo and indomethacin. SUBJECTS: Thirty nine healthy subjects (aged 24–30 years). METHOD: We performed a four period crossover trial to assess intestinal permeability before and after seven days of treatment. Permeability was measured by the urinary ratio of chromium-51 labelled ethylene diamine tetraacetate ( 51 CrEDTA)/l -rhamnose (five hour collection). RESULTS: Indomethacin 50 mg three times daily produced greater increases in intestinal permeability compared with placebo or rofecoxib (25 or 50 mg) (p⩽0.001); rofecoxib was not significantly different from placebo. Mean day 7 to baseline ratios (95% confidence intervals) for 51 CrEDTA/l -rhamnose were 0.97 (0.82, 1.16), 0.80 (0.68, 0.95), 0.98 (0.82, 1.17), and 1.53 (1.27, 1.85) for placebo, rofecoxib 25 mg, rofecoxib 50 mg, and indomethacin groups, respectively. Rofecoxib was generally well tolerated. CONCLUSION: In this study, treatment for one week with indomethacin 50 mg three times daily significantly increased intestinal permeability compared with placebo, while treatment with rofecoxib 25 mg or 50 mg daily did not. The absence of a significant effect of rofecoxib on intestinal permeability at doses at least twice those recommended to treat osteoarthritis was consistent with other studies that have demonstrated little or no injury to the gastrointestinal mucosa associated with rofecoxib therapy.